Dynamics of irrigation institutions: case study of a village panchayat in Kerala - Menon, Vineetha; Nair, K.N.; Paul, Antonyto (2005)
Based on field work in a village panchayat in Kerala that analysed the complex issues concerning the development and working of irrigation institutions, the present study reveals that successful management of irrigation is contingent upon the level of participation of the water users in management. By comparing irrigation institutions under different property rights, the study identifies the significant factors that contribute to the success and sustainability of irrigation institutions. It is found that albeit the physical characteristics of irrigation systems and the heterogeneities of the members of the user groups do have an impact on the outcome, it is the institutional environment as reflected in the presence of clear as well as flexible systems of rules and regulations, enforcement mechanisms, nesting and networking of such institutions, etc. that have become the most crucial determinants. - Reproduced.
Keywords: Irrigation - India - Kerala; Irrigation